S-ethyl ethanethiosulfinate, a derivative of allicin, induces metacaspase-dependent apoptosis through ROS generation in Penicillium chrysogenum. Issue 6 (14th June 2019) - Qi, Feilong; Zhang, Chen; Jiang, Shanshan; Wang, Qian; Kuerban, Kudelaidi; Luo, Man; Dong, Mengxue; Zhou, Xinguang; Wu, Laiming; Jiang, Biao; Ye, Li
Abstract : Allicin can be used as fumigant to protect food and cultural relics from fungal contamination because of its strong antifungal activity and the characteristics of high volatility and no residues. However, the obvious disadvantages such as high minimal inhibitory concentration and instability prevent it from wide application. In this study, a stable derivative of allicin, S -ethyl ethanethiosulfinate (ALE), was synthesized. We further explored its antifungal activity and apoptosis-inducing effect, as well as the underlying mechanism. ALE had an excellent capability of inhibiting spore germination and mycelial growth of Penicillium chrysogenum observed by inverted microscope and scanning electron microscopy. XTT colorimetric assay indicated ALE could reduce the cell viability obviously and IC50 was 0.92 μg/ml, only 1/42 of allicin (38.68 μg/ml). DHR 123 ROS Assay Kit, flow cytometry assay and confocal immunofluorescence revealed intercellular ROS generation and metacaspase-dependent apoptosis triggered by ALE, while antioxidant tocopherol could reverse ALE-induced cytotoxicity effect and metacaspase activation. These results indicate that ALE induces metacaspase-dependent apoptosis through ROS generation, thus possesses an effective antifungal activity . This new derivative of allicin might be developed as a high efficient alternative to the conventional fungicides for food storage and cultural relic protection.